ENERGI LISTRIK DARI SEDIMEN LAUT TELUK JAKARTA MELALUI TEKNOLOGI MICROBIAL FUEL CELL - Bambang Riyanto; Nisa Rachmania Mubarik; Fitriani Idham (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Sediment microbial fuel cell (SMFC) is one form of the microbial fuel cell (MFC) that can convert organic complex material in the sediment to generate electrons. This research was conducted to determine the characteristicsof marine sediments from the Bay of Jakarta, to know the amount of electric current can be generated through SMFC, and to identify bacteria at the anode SMFC. This research was conducted in several stages which include the characterization of marine sediment samples, making SMFC circuit, electric current measurement, characterization SMFC substrate, and the isolation, characterization, and identi cation of bacteria. The study shows that marine sediments of Jakarta Bay have characteristics which include silty clay loam texture, organic carbon 2.19%, total nitrogen 0.19%, and phosphorus 128 ppm. The electric current generated by the SMFC using  xed value resistors 820 Ω ± 5% reach peak production of electric currents on day 21, that is 139.51 mA/m2 with SMFC substrate having organic carbon 1.88%, total nitrogen 0.15%, and phosphorus 88 ppm. Isolation of bacteria at the anode was found three types of isolates, that suspected are Aeromonas hydrophila, Acinetobacter sp., and Bacillus marinus.Keywords: electrical energy, Jakarta bay, marine sediment, sediment microbial fuel cell